Confinement-deconfinement transition due to spontaneous symmetry breaking in quantum Hall bilayers - D. I. Pikulin (Nature Portfolio, 2016)
Electronic systems with inverted band structures can support exotic topological insulator and exciton condensate states. Here, the authors demonstrate the formation of a helical exciton condensate in quantum Hall bilayers, and a quark-like quasiparticle confinement-deconfinement transition.